An Analysis Language Style Based on The Level of Formality According To Martin Joos Theory - Para pean silta; Godefridus Bali Geroda; Widi Syahtia Pane (Wadah Inovasi Indonesia, 2023)
Background: This study discusses the style of language used in the movie Home Alone 2. The purpose of this study is to find out what style of language is applied in the movie